RNA-Sequencing Reveals Heat Shock 70-kDa Protein 6 (HSPA6) as a Novel Thymoquinone-Upregulated Gene That Inhibits Growth, Migration, and Invasion of Triple-Negative Breast Cancer Cells - Shen, Shiyi; Wei, Chunli; Fu, Junjiang (Frontiers in Oncology, 2021)
Objective: Breast cancer has become the first highest incidence which surpasses lung cancer as the most commonly diagnosed cancer, and the second highest mortality among women worldwide. Thymoquinone (TQ) is a key component from black seed oil and has anti-cancer properties in a variety of tumors, including triple-negative breast cancer (TNBC). Methods: RNA-sequencing was conducted with and without TQ treatment in TNBC cell line BT-549. Gene Ontology (GO) function classification annotation, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses for these genes were conducted. Western blot and semi-quantitative RT-PCR were used to verify the regulated gene. Functional assays by overexpression or knocking down were performed for HSPA6 and its mediator TQ for inhibiting growth, migration and invasion of TNBC cells. The regulatory mechanisms and prognosis for HSPA6 for breast cancer survival were conducted through bioinformatics and online databases. Results: As a result, a total of 141 downregulated and 28 upregulated genes were identified and 18 differentially expressed genes, which might be related to carcinomas, were obtained. Interestingly, GO and KEGG pathway showed their roles on anti-cancer and anti-virus. Further analysis found that the HSPA6 gene was the high significantly upregulated gene, and showed to inhibit TNBC cell growth, migration and invasion. High expression of HSPA6 was positively correlated with long overall survival (OS) in patients with breast cancer, indicating the tumor-suppressive roles for HSPA6. But DNA methylation of HSPA6 may not be the regulatory mechanism for HSPA6 mRNA upregulation in breast cancer tissues, although the mRNA levels of HSPA6 were increased in these cancer tissues compared with normal tissues. Moreover, TQ enhanced the inhibitory effect of migration and invasion when HSPA6 was overexpressed; while HSPA6 was knocked down, TQ attenuated the effects of HSPA6-promoted migration and invasion, demonstrating a partially dependent manner through HSPA6 by TQ. Conclusion: We have successfully identified a novel TQ-targeted gene HSPA6, which shows the inhibitory effects on growth, migration and invasion in TNBC cells. Therefore, identification of HSPA6 not only reveals a new TQ regulatory mechanism, but also provides a novel candidate gene for clinical management and treatment of breast cancer, particularly for TNBC.